About the Сreative Path of V. S. Baranovsky - Potashenko, Grigorii (Literatūra, 2025)
The article examines the main stages of the work of the writer and historian of Old Believers Vasily Baranovsky and the significance of his work in the public discourse of Lithuania against the backdrop of changing eras. In the 1970s and 1980s, the Old Believers of Lithuania first became the object of closer attention of some Russian and Lithuanian prose writers and poets. A special role in this belongs to the prose writer V. Baranovsky.The prose and poetry of V. Baranovsky, dedicated to the Old Believers and their figures, which was created in the 1990s – early 2020s, stands apart. He largely shapes the literary Russian-language discourse on the Old Believers in Lithuania and remains an almost lonely prose writer in it. The literary work of V. Baranovsky, as a popularization of the history of the Old Believers in Lithuania and Latvia, is something more than fine literature or evidence of past eras. This is a look at history in the light of conscience and culture.